First discovery of Holocene Alaskan and Icelandic tephra in Polish peatlands. (May 2017) - Watson, E. J.; Kołaczek, P.; Słowiński, M.; Swindles, G. T.; Marcisz, K.; Gałka, M.; Lamentowicz, M.
ABSTRACT: Despite the discovery of cryptotephra layers in over 100 peatlands across northern Europe, Holocene cryptotephra layers have not previously been reported from Polish peatlands. Here we present the first Holocene tephra findings from two peatlands in northern Poland. At Bagno Kusowo peatland we identify the most easterly occurrence of the AD 860 B tephra, recently correlated to the White River Ash (WRAe) derived from Mount Churchill, Alaska. A shorter core from Linje peatland contains tephra from the Askja 1875 eruption, extending the spatial distribution and regional importance of this Icelandic tephra in Eastern Europe. Our research indicates the potential of cryptotephra layers to date and correlate the growing number of palaeoenvironmental studies being conducted on Polish peatlands and contributes towards the development of a regional Holocene tephrostratigraphy for Poland. Copyright © 2017 The Authors. Journal of Quaternary Science Published by John Wiley & Sons, Ltd.